Resposta :
Resposta:
2/[√(3-√5) ]=2[√(3-√5) ]/{[√(3-√5) ]*[√(3-√5) ]}
= 2[√(3-√5) ]/(3-√5)
= 2[√(3-√5) ]*(3+√5)/[(3-√5)*(3+√5) ]
= 2√(3-√5) *(3+√5)/(3²-√5²)
= 2√(3-√5) *(3+√5)/(9-5)
= 2√(3-√5) *(3+√5)/4
= [√(3-√5)] *(3+√5)/2
[tex]\frac{2}{\sqrt{3-\sqrt{5} }} =\frac{2}{\sqrt{3-\sqrt{5} }} \cdot\frac{\sqrt{3+\sqrt{5}}}{\sqrt{3+\sqrt{5}}} =\frac{2\cdot\sqrt{3+\sqrt{5}}}{\sqrt{3^2-(\sqrt{5})^2}} =\frac{2\cdot\sqrt{3+\sqrt{5}}}{\sqrt{9-5}} =\frac{2\cdot\sqrt{3+\sqrt{5}}}{\sqrt{4}}} \\\\=\frac{2\cdot\sqrt{3+\sqrt{5}}}{2}} =\sqrt{3+\sqrt{5}}}[/tex]